#Je suis Charlie: Networks, Affects and Distributed Agency of Media Assemblage - Salovaara, Inka (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This paper analyses the Je suis Charlie movement as an affective assemblage. It looks at digital network activism around the Charlie Hebdo shootings in the perspective of the Deleuzian concepts of assemblage and event. The essay argues that new participatory activism can be understood in two ways: as a (territorialised) ‘assemblage’ (after Delanda, 2006) and as a constellation of ‘things’ into what Thrift (2007) calls a ‘transient structure’ (Salovaara 2014). Drawing from assemblage theory (Deleuze & Guattari 1996; DeLanda 2006), the essay explores concrete and virtual sides of a media assemblage as event spaces. Empirically, the analysis explores the assemblage, as well as related memes, hashtags and narratives around #Je suis Charlie activism.